Botanical composition and nutritive value of the available forage and diet selected by water buffaloes in Brachiaria humidicola pasture - Camarão, Ari Pinheiro; Batista, Heriberto Antonio Marques; Junior, José de Brito Lourenço; Rodrigues, Luis Roberto de Andrade; Malheiros, Euclides Braga (Pesquisa Agropecuaria Brasileira, 1994)
Aiming to evaluate the botanical composition and nutritive value (crude protein-CP and in vitro organic matter digestibility-IVOMD) of the available forage and diet selected by water buffaloes in B. humidicola pasture, an experiment was carried out in Belém, PA, Brazil. Diet samples were taken from esophageal fistulated water buffaloes and the available forage was taken by cut. The botanical composition of the diet subsamples was sorted into four parts: leaves (L.), stems (S), dead material (D) and other plants (OP). The experimental design was a completely random one for pasture data and a randomized block for animal diet. The availability of SD and total forage, the botanical composition, and the nutritive value of the diet and available forage were affected by season and month of the year. L% in the diet was higher, while S % and D % were smaller. CP % and IVOMD of diet were higher than L and S. The results showed that water buffaloes graze selectively as the other ruminants.